Modulating effects of Ukrainian phytocomposition "Balm Truskavets'" on post stress changes in neuroendocrine-immune complex, metabolome, electrocardiogram, and gastric mucosa at rats - Walery Zukow; Oksana Fihura; Mykhaylo Korda; Ivan Klishch; Sofiya Ruzhylo; Oksana Melnyk; Roman Yanchij; Igor Popovych (Kazimierz Wielki University, 2024)
Introduction and aim. Earlier our group showed that the Ukrainian phytocomposition "Balm Truskavets'" (UPhCBT) exerts classical adaptogenic effects on parameters of neuro-endocrine-immune complex as well as biophotonics and acupuncture in humans with maladaptation. The list of important properties of adaptogens includes their stress-limiting effect, which is usually tested in an experiment. Therefore, the purpose of this study was to identify modulating effects of UPhCBT on post-stress changes in neuro-endocrine-immune complex, metabolome, electrocardiogram (ECG), and gastric mucosa at rats. Material and methods. The experiment is at 18 male and 20 female Wistar rats. 10 animals remained intact with free access to tap daily water. Rats of the control group for 7 days loaded through a tube with same tap daily water (2 mL once), while the animals of main groups received according to a similar scheme 0,1 mL of PhCBT dissolved in 2 mL of daily water or bottled table water "Truskavetska"™. Over the next 10 days, one animal remained intact and 3 other rats were exposed to acute (4 hours) water-immersion and restraint stress. The next day after stressing, EEG, endocrine, immune and metabolic parameters as well as gastric mucosa injuries was recorded. Results. Acute stress causes in control animals an increase in sympathetic tone, serum levels of catecholamines and corticosterone, combined with a decrease in vagal tone and serum testosterone levels. Such a neuro-endocrine reaction is accompanied by damage to the myocardium and gastric mucosa, an increase in the percentage of macrophages and fibroblasts in the thymus, entropy in the spleen, natural killer cells in the blood. Instead, the mass of the spleen and the percentage of lymphoblasts in it, theophylline-sensitive T-lymphocytes in the blood, the content of α-LP cholesterol in the serum, as well as the catalase and Na,K-ATPase activity of erythrocytes, decrease. Preventive use of phytocomposition, first of all, minimizes or even completely prevents damage to the myocardium and adverse post-stress deviations from the norm of listed parameters. Secondly, it initiates an increase in the level of PTH and the activity of serum acid phosphatase, the percentage of reticulocytes in the spleen and the intensity of phagocytosis of blood neutrophils, but at the same time a decrease in their bactericidal activity, as well as the percentage of monocytes and B-lymphocytes in the blood. Thirdly, it potentiates the post-stress increase in sympathetic tone and damage to the gastric mucosa, as well as natural killers, on the one hand, and the decrease in vagal tone, the level of testosterone in the serum, as well as the mass of the spleen - on the other hand. Fourthly, it reverses the activity of catalase of erythrocytes and the entropy of the splenocytogram. Conclusion. Ukrainian phytocomposition "Balm Truskavets" has a generally favorable adaptogenic effect on the post-stress state of the neuro-endocrine-immune complex and metabolome. However, there are certain adverse effects as the so-called adaptation fee.